Synthesis of N-iodosuccinimide and its application in H2SO4 as efficient iodination reagent for deactivated aromatic compounds; Russian Journal of Organic Chemistry; Vol. 37, iss. 10 - Chaikovskii V. K. (2001, 2001)
Title screen